Revision of the Griburius scutellaris (Fabricius, 1801) species group (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2023)
Ten species of Griburius Haldeman, 1849, morphologically similar to each other, and some of their synonyms are revised, figured and discussed. Among them is G. scutellaris (Fabricius, 1801), the type species of Griburius. Seven of the studied species are already described: Griburius albilabris (Suffrian, 1852), Griburius boucardi (Jacoby, 1880), Griburius errans (Suffrian, 1852), Griburius larvatus Newman, 1840, Griburius lecontii Crotch, 1873, Griburius montezuma (Suffrian, 1852) and Griburius scutellaris (Fabricius, 1801). In addition, Griburius biverrucatus (Suffrian, 1852) stat. restored and Griburius decoratus (Suffrian, 1852) stat. restored, formerly considered conspecific of G. albilabris and G. larvatus, respectively, are here resurrected to full species status. Griburius spadiceus (Suffrian, 1852) syn. nov. is transferred from the synonymy with G. larvatus to the synonymy with G. decoratus. In addition, the following new or restored synonymies are proposed: G. albilabris (= G. suturalis (Suffrian, 1852) syn. restored; = G. zonatus (Suffrian, 1852) syn. restored); G. montezuma (Suffrian, 1852) (= G. cazicus (Suffrian, 1852) syn. nov.; = G. suffriani (Jacoby, 1880) syn. restored). Lastly, Griburius rileyi sp. nov. is described as new to science. The lectotypes of all previously described valid species and the confirmed synonyms are designated. The new synonymies, the name-bearing type fixations and designations and the nomenclatural acts are critically discussed. An identification key for the species-group is also provided.